Assessment of genetically modified maize MON 89034 × 1507 × NK603 for renewal authorisation under Regulation (EC) No 1829/2003 (application GMFF‐2022‐3670) - EFSA Panel on Genetically Modified Organisms (GMO); Ewen Mullins; Jean‐Louis Bresson; Tamas Dalmay; Ian Crawford Dewhurst; Michelle M. Epstein; Leslie George Firbank; Philippe Guerche; Jan Hejatko; Francisco Javier Moreno; Hanspeter Naegeli; Fabien Nogué; et al. (EFSA Journal, 2024)
Abstract Following the submission of dossier GMFF‐2022‐3670 under Regulation (EC) No 1829/2003 from Corteva Agriscience Belgium BV and Bayer Agriculture BV, the Panel on genetically modified organisms of the European Food Safety Authority was asked to deliver a scientific risk assessment on the data submitted in the context of the renewal of authorisation application for the herbicide‐tolerant and insect‐resistant genetically modified maize MON 89034 × 1507 × NK603, for food and feed uses, excluding cultivation within the European Union. The data received in the context of this renewal application contained post‐market environmental monitoring reports, a systematic search and evaluation of literature, updated bioinformatic analyses and a search for additional documents or studies performed by or on behalf of the applicant. The GMO Panel assessed these data for possible new hazards, modified exposure or new scientific uncertainties identified during the authorisation period and not previously assessed in the context of the original application. Under the assumption that the DNA sequences of the events in maize MON 89034 × 1507 × NK603 considered for renewal are identical to the sequences of the originally assessed events, the GMO Panel concludes that there is no evidence in renewal dossier GMFF‐2022‐3670 for new hazards, modified exposure or scientific uncertainties that would change the conclusions of the original risk assessment on maize MON 89034 × 1507 × NK603.